Methodology for pH measurement in high alkali cementitious systems. (September 2020) - Traynor, Brian; Uvegi, Hugo; Olivetti, Elsa; Lothenbach, Barbara; Myers, Rupert J.
Abstract: A methodology for calibrating pH meters in highly alkaline solutions such as those relevant to cementitious systems is presented. This methodology uses an extended form of the Debye-Hückel equation to generate a calibration curve of pH vs. the measured electrochemical potential (mV) based on a series of aqueous alkali hydroxide solutions of known concentrations. This methodology is compared with the 'built-in' process of calibration based upon pH 4, 7, and 10 standard solutions. The built-in calibration process underestimates the real pH values by up to 0.3 log units, which is attributed to the alkali error. A spreadsheet for determining the calibration curve and its application to pH meter readings is provided as Supporting Information. The implications of improperly calibrated pH meters on interpreting solution chemistry in cementitious systems are discussed.